Studi Ragam Morfologi Polen Mangga (Mangifera sp.) Di Kecamatan Loa Janan Kabupaten Kutai Kartanegara - Abdullah, Agni Pusparina Putri; Syafrizal, Syafrizal; Susanto, Dwi (BIOPROSPEK: Jurnal Ilmiah Biologi, 2019)
Conducted in March to May 2018, sampling was conducted in Loa Janan Sub-district, Kutai Kartanegara District and further observations were made at Anatomy and Plant Systematic Laboratory, Faculty of Mathematics and Natural Sciences Mulawarman University. Pollen preparations are prepared by the method of acetolysis. This study obtained 7 mango cultivar that were flowering and the morphology of pollen obtained had monad shape and spheroidal prolate size by calculating index of polar axis and equatorial axis. While the variations of the ornaments are regulate and reticulate, the aperture is inaperture and monosulcate. Mango pollen has a spheroidal prolate size with a P / E index of 1.00 to 1.14.